Management of Blunt Trauma to the Spleen (Part 2) - Seyed Abbas Banani (Iranian Journal of Medical Sciences, 2010)
Spleen is the most frequently-injured solid organ in blunt abdominaltrauma. Considering its important role in providingimmunity and preventing infection by a variety of mechanisms,every attempt should be made to salvage the traumatizedspleen at any age particularly in children. After primaryresuscitation, mandatory requirements for non-operative managementinclude absence of homodynamic instability, lack ofassociated major organ injury, and admission in the intensivecare unit for high-grade splenic injury and in the ward formilder types with close monitoring. About two-thirds of thepatients would respond to non-operative management. In mostpatients, the failure of non-operative measures usually occurswithin 12 hours of management. Determinant role of abdominalsonography or computed tomography, and in selectedcases, diagnostic peritoneal lavage, for appropriate decisioncannot be overemphasized. However, the high status of clinicaljudgment would not be replaced by any paraclinical investigations.When operation is unavoidable, if possible, spleensaving procedures such as splenorrhaphy or partial splenectomyshould be tried. In cases of total splenectomy, autotransplantation,preferably in the omental pouch, may lead tothe return of immunity, at least partially, to prevent or reducethe chance of subsequent infection. Although total splenectomywith autograft is immunologically superior to total splenectomy-only procedure, the patients should also be protectedby vaccination and daily antibiotic for certain period of time.The essential steps for the prevention of overwhelming infectionafter total splenectomy are not only immunization and administrationof daily antibiotic for up to 5 years of age or oneyear in older children, but also include education and informationabout this dangerous complication. When non-operativemanagement is successful, the duration of activity restriction inweeks is almost equal to the grade of splenic injury plus 2.